Dystocia Due to Secondary Partial Uterine Inertia in a New Zealand White Rabbit - Narwade , Priyanka; Balamurugan , B.; Mishra , R.M.; Kumar , Vinod; Ravi, S.K; Kumar , P. R; Jena , Dayanidhi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
A one-year-old Doe weighing 1.2 kg was brought to Teaching Veterinary Clinical Complex, FVAS, BHU-Mirzapur, with a history of giving birth to three dead bunnies 3 days before and after that not show any signs of kindling. Vulvul lips were swollen, congested and edematous. The Perineal area was smeared with uterine discharge. Doe had Inappetence dehydration for 3 days. Doe was previously treated with inj. oxytocin @ 1 to 3 IU I/M and inj. Epidosin @ 8mg/ kg I/M along with calcium gluconate @ 0.25 ml/kg slow I/V before 24 hrs. Abdominal palpation revealed the presence of fetal mass. Lateral abdominal radiograph showed the presence of one fetus’s skeleton located in the pelvic cavity. Based on the history and obstetrical examination it was diagnosed as a case of dystocia due to secondary partial uterine inertia. A male dead bunny was relived through exploratory laparotomy under general anaesthesia (premeditated with inj. xylazine 5 mg/kg body weight and induction with isoflurane 3-5%). Doe had an uneventful recovery following exploratory laparotomy with proper postoperative care. Dystocia due to secondary partial uterine inertia is a rare case in rabbits and it can be managed through exploratory laparotomy with proper post-operative care.